Rockfall Hazard Assessment Around Ankara Citadel (Turkey) Using Rockfall Analyses and Hazard Rating System - San, Nyein Ei; Topal, Tamer; Akin, Muge K. (Springer, 2020)
Ankara Citadel which is one of the important cultural heritages in Turkey settles in the oldest part of Ankara. Rockfall event has occurred around the Citadel located on a steep hill where andesite is exposed. The rockfall problem causes a great risk to the surrounding area where road, school, floral shops, car parking. Therefore, the major aim of this research is to reveal the rockfall risk around the castle. The rockfall problems around the Ankara Citadel may be linked with weathering, freezing-thawing, earthquake, and cooling joints, and effects or combination of these in the rock units. The rockfall-related hazard at the Citadel is assessed by 2-D rockfall analyses along several profiles in this investigation. Field observations and stability analyses (kinematic and limit equilibrium) of the slopes reveal that there exist many blocks ready to fall down. Four different andesite block sizes measured in the field are separately analyzed on the basis of bounce height, fall-out distance, velocity and kinetic energy of the blocks. The obtained data are evaluated to define the possible rockfall-based hazard zones. Based on the danger zones acquired from the rockfall analyses, the removal of the fallen and loosen andesite blocks and the installation of catch barriers with suggested properties are recommended. Besides, the risk integrated into rockfall hazard rating system on the basis of structural and morphological criteria of the rock mass reveals that medium risk category to be mitigated by light remedial measures for the indicative protection exists in the study area.
Keywords: Andesite; Ankara Citadel; Rockfall Analysis; Zonation Map; Turkey; Rockfall Hazard Rating System